PENGEMBANGAN LEMBAR KERJA SISWA DENGAN STRATEGI PQ4R PADA MATERI GENETIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA KELAS XI SMKN PERTANIAN TERPADU PROVINSI RIAU TAHUN AJARAN 2015/1016 - Nora Fitria; Evi Suryawati; Darmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : According Permendikbud number 81A, one of the competence of the future needed is the ability to think critically. Therefore, it was expected the field of education focused on the fulfillment of these competencies. The purposed of this research was to develop students' worksheets with PQ4R strategies on genetic material to improve the critical thinking skills of students in Class XI SMKN Integrated Agricultural Riau Province. This research was conducted at the Laboratory of Biology Department of the PMIPA FKIP University of Riau and SMKN of Agriculture in May to October 2016. This type of research was the development of research using ADDIE model of integration to the stage of development. There were 3 worksheets developed. Instruments of data collection in this study were the validation sheet worksheets, student questionnaire responses, and critical thinking skills observation sheet. After LKS developed, the tests I on 16 students of fourth semester of biology education FKIP UR, then validated by the validator 4, and a second trial on 31 students. I result showed the average score 3,53 with very good category. The tests showed the average score of 3 LKS design developed was 3,08 valid category, the mean score of the pedagogic aspect was 3,21 valid category, and the mean score of the content aspect was 3,30 very valid category. The mean score of all aspects of the three categories 3,20 LKS was valid. II result showed the average score 3,36 with very good category. The results of the analysis of the answers of students in Worksheet 1 showed the mean value of 3.61. Based on the results of data analysis could be concluded that the development of the Strategy Worksheet PQ4R the genetic material increased the understanding and knowledge of the genetic material and enhanced students' critical thinking skills.